PENATAAN PEDAGANG KAKILIMA (PKL) DI KAWASAN TAMAN RIA PALU - Nindyo Soewarno; Muhammad Bakri (Jurnal Green Growth dan Manajemen Lingkungan, 2012)
AbstractThe matter of retail traders (PKL) is one of the classical problems that always be a problem for an area or region at it results a bad image for the area where which they take place. Such a condition happens in Taman Ria Palu area. The condition has caused bad effect that is especially in the space usage of the area, uncontrolled growth and no specific form for PKL. Such a condition must be solved through out research that emphasizing at the form and the use of the space of the area by PKL It is in order to identify the problems of the element of the problems so that can help the development of the area. The advantage of the research is so that the PKL do not become a problem for the element of the area they take place but to find a solution point of the problem at the area that have a link with PKL's activities. It's can be a contribution for the government to arrange the government regulation. The analysis of this research employs the theory of need of that people in visiting the area (park) and see the PKL as one of the components of the space order together with the other ones. The frame of the theory that used is by observing the interaction among public area, public activity, and the activity of all PKL in using the area. This research is using the method of descriptive qualitative quantitative paradigm that explain the qualitative data in form of matrix, picture to find out the parameter, variable, and the research indicator based on the frame of theory. The result of the research that have link with the pattern of the development of PKL is uncontrolled, activity as the respond of the growth, and the intraction among elements of the area strongly effects the need of people for visiting the area (the park). The factor influenced the use of the are must reviewed in the terms of designing patterns for solving the problem.